COVID-19–Related Changes in Assistance Networks for U.S. Older Adults With and Without Dementia. (16th July 2022) - Brown, Monique J; Wang, Haowei; Lin, I-Fen; Gan, Daniel; Oyeyemi, Deborah; Manning, Mark; Freedman, Vicki A
Abstract: Objectives: Prepandemic research suggests assistance networks for older adults grow over time and are larger for those living with dementia. We examined how assistance networks of older adults changed in response to the onset of the coronavirus disease 2019 (COVID-19) pandemic and whether these changes differed for those with and without dementia. Methods: We used 3 rounds of the National Health and Aging Trends Study. We estimated multinomial logistic regression models to test whether changes in assistance networks during COVID-19 (2019–2020)―defined as expansion, contraction, and adaptation―differed from changes prior to COVID-19 (2018–2019). We also estimated ordinary least squares regression models to test differences in the numbers of helpers assisting with one (specialist) versus multiple (generalist) domains before and during COVID-19. For both sets of outcomes, we investigated whether pandemic-related changes differed for those with and without dementia. Results: Over all activity domains, a greater proportion of assistance networks adapted during COVID-19 compared to the pre-COVID-19 period (relative risk ratio = 1.19, p < .05). Contractions in networks occurred for those without dementia. Transportation assistance contracted for those with and without dementia, and mobility/self-care assistance contracted for those with dementia. The average number of generalist helpers decreased during COVID-19 (β = −0.09, p < .001). Discussion: Early in the pandemic, assistance networks of older adults adapted by substituting helpers, by contracting to reduce exposures with more intimate tasks for recipients with dementia, and by reducing transportation assistance. Future research should explore the impact of such changes on the well-being of older adults and their assistance networks.